A Flipped Classroom Approach to Teaching Engineering Mechanics Courses - Sirigiri, M.; Rajan, S. D. (Journal of Engineering Education Transformations, 2015)
A flipped classroom approach to teaching engineering mechanics courses taught in the 2nd and 3rd year of a typical undergraduate engineering education, is explained. A combination of few lectures supported by several problem solving recitation classes and continuous assessment, provides both the students and the instructional team an accurate, dynamic picture of the students’ understanding and performance. Early use of computer code and openended projects strengthens the understanding of analysis and design techniques in the context of engineering analysis and design. Experience from teaching a 3rd year (junior level) structural analysis and design class for over two decades is shared to draw appropriate conclusions.